The presidency in the era of 24-hour news - Cohen, Jeffrey E. (Princeton University Press, 2008)
The Presidency in the Era of 24-Hour News examines how changes in the news media since the golden age of television--when three major networks held a near monopoly on the news people saw in the United States--have altered the way presidents communicate with the public and garner popular support. - Publisher.
Keywords: USA -- Präsident; Presidents -- United States.; Mass media -- Political aspects -- United States.; Press and politics -- United States.; Presidents -- Press coverage -- United States.; United States -- Politics and government -- Press coverage.; Présidents -- États-Unis.; États-Unis -- Politique et gouvernement -- Couverture de presse.; POLITICAL SCIENCE -- Political Process -- Leadership.; SOCIAL SCIENCE -- Media Studies.; Mass media -- Political aspects; Politics and government -- Press coverage; Presidents; Presidents -- Press coverage; Press and politics; United States; Massenmedien; Berichterstattung